The Impact of Digitalization and the Quality of the P3-TGAI Monitoring Application’s Information System on the Effectiveness and Accountability of Irrigation Management at the Sulawesi V Mamuju River Basin Office - Fitriani; Naluria Islami; Hari Yeni; Muhammad Aqil (Research and Social Study Institute (ReSSI), 2026)
The digitalization of water resources management is a strategic necessity to accelerate the monitoring process, enhance information accuracy, and increase the transparency of government program implementation. This study aims to analyze the effect of digitalization and the quality of the monitoring application information system for the Irrigation Water Use Acceleration Improvement Program (P3-TGAI) on the effectiveness and accountability of irrigation management at the Sulawesi V Mamuju River Basin Office. The study used a quantitative approach with an explanatory design. Data were collected through a Likert-scale questionnaire to 60 respondents consisting of BWS technical staff, P3A technical assistants, administrators of water user farmer organizations, and structural officials who use the application. Data were analyzed using Structural Equation Modeling–Partial Least Squares with the help of SmartPLS 4.0. The results showed that digitalization had a positive and significant effect on effectiveness with a path coefficient of 0.341, a t-statistic of 3.214, and a p-value of 0.001. Digitalization also had a significant effect on accountability with a coefficient of 0.289, a t-statistic of 2.876, and a p-value of 0.004. Information system quality has the strongest influence on effectiveness with a coefficient of 0.412, a t-statistic of 4.508, and a p-value <0.001, and an impact on accountability with a coefficient of 0.377, a t-statistic of 3.962, and a p-value <0.001. Digitalization and information system quality explain 64.2% of the variation in effectiveness and 58.7% of the variation in accountability. This study concludes that an integrated, stable, easy-to-use monitoring application that produces accurate information can improve program coordination, control, reporting, transparency, and accountability. Strengthening digital infrastructure, user competency, system security, and data validation should be a priority in realizing effective, accountable, and sustainable P3-TGAI governance.